Single-port-plus-one robot-assisted laparoscopic modified Lich-Gregoir direct nipple ureteral extravesical reimplantation in children with a primary obstructive megaureter - He, Yufeng; Lin, Shan; Xu, Xinru; He, Shaohua; Xu, Huihuang; You, Guangxu; Chen, Jianglong; Xu, Di (Frontiers in Pediatrics, 2023)
To introduce a new technique of single-port-plus-one robotic laparoscopic modified Lich-Gregoir direct nipple ureteral extravesical reimplantation and verify its validity in the treatment of pediatric primary obstructive megaureter. Methods: Retrospectively analyzed the clinical data of 12 children with primary obstructive megaureter admitted to the Department of Pediatric Surgery of Fujian Provincial Hospital from January 2021 to November 2021. 12 children were treated with single-port-plus-one robotic laparoscopic Lich-Gregoir direct nipple ureteral extravesical reimplantation. Five of them were female and seven were male, including nine obstructive cases and three obstructive with reflux cases. The mean age was 17.33 ± 6.99 (10-36) months and the mean follow-up time was 14.16 ± 1.75 (12-17) months. Changes in parameters preoperative and 1 st year postoperative were compared. Results: The mean operative time for the 12 children was 123.58 ± 10.85 (110-145) min, with a mean internal operative time of 101.42 ± 0.85 (90-120) min, mean operative bleeding of 2.42 ± 0.67 (2-4) ml and mean haematuria duration of 16.08 ± 1.44 (14~19) hours, mean Indwelling catheterization time was 2.25 ± 0.45 (2~3) days and mean hospitalization were 3.83 ± 0.39 (3~4) days. At 1 st year postoperative, the ureteral diameter, calyceal diameter, and APRPD were significantly smaller than preoperative (18.83 ± 3.21 mm vs 6.83 ± 1.27 mm, 13.99±3.58mm vs 3.5±2.90mm and 34.92 ± 4.25 mm vs 10.08 ± 1.88 mm, P<0.001). Renal cortical thickness and DRF % were significantly increased (3.63±1.66mm vs 5.67±1.88mm,33.75 ± 2.77 mm vs 37.50 ± 1.31 mm, P <0.001). The resolution rate of obstruction was 100% and no one develop developed DeNovo VUR. Conclusion: The technique of modified Lich-Gregoir direct nipple ureteral extravesical reimplantation can remain maintain the physiological direction of the ureter and enhance the effectiveness of anti-refluxing at the same time in robot surgery. The design of a single-port-plus-one wound can produce a cosmetic appearance by concentrating and hiding the wound around the umbilicus. This modified surgery may become a promising used surgery in the robot-assisted treatment of POM.